2016
DOI: 10.1016/j.ypmed.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening in Switzerland: 20-year trends and socioeconomic disparities

Abstract: Despite important controversy in its efficacy, prostate cancer (PCa) screening has become widespread. Important socioeconomic screening disparities have been reported. However, trends in PCa screening and social disparities have not been investigated in Switzerland, a high risk country for PCa. We used data from five waves (from 1992-2012) of the population-based Swiss Health Interview Survey to evaluate trends in PCa screening and its association with socioeconomic indicators

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 55 publications
7
39
0
1
Order By: Relevance
“…However, Fedewa et al found no significant differences in the likelihood of screening between smokers and non‐smokers in Switzerland. The findings on the effect of smoking on screening tests in the present study are consistent with those of Guessous et al, Sing et al and So et al Perhaps because smoking causes serious deteriorations in health, individuals who take less care of their health are also more oblivious to the importance of health screening. The policy implication is that improving health awareness among elderly smokers is necessary to increase the prevalence of blood glucose screening.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, Fedewa et al found no significant differences in the likelihood of screening between smokers and non‐smokers in Switzerland. The findings on the effect of smoking on screening tests in the present study are consistent with those of Guessous et al, Sing et al and So et al Perhaps because smoking causes serious deteriorations in health, individuals who take less care of their health are also more oblivious to the importance of health screening. The policy implication is that improving health awareness among elderly smokers is necessary to increase the prevalence of blood glucose screening.…”
Section: Discussionsupporting
confidence: 92%
“…The effects of income on health screening have been examined in a few empirical studies, 8,11,28 and the outcomes reported therein are consistent with the findings of the present study. Lairson et al 8 found that income Blood glucose screening Y.K.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Language region of residence was added to the models due to known regional differences in lifestyle-associated risk factors (i.e. alcohol and tobacco consumption [27]), screening behaviour [28,29] and treatment regimens [30].…”
Section: Methodsmentioning
confidence: 99%
“…В США с 1992 по 2012 г. частота скрининга выросла с 55,3 до 70,0 % [9].В Швейцарии было отмечено, что частота скрининга отличалась в зависимости от уровня образованности, профессии. Так, например, она была выше среди населения с вы-соким доходом (> 6000 долларов США в месяц) по сравнению с людьми с низким доходом (< 2000 дол-ларов США в месяц) [10].…”
Section: Introductionunclassified